ADVERSE SOCIAL EXPERIENCES, SOCIAL SUPPORT, AND HEALTH OUTCOMES AMONG BLACK AND WHITE FAMILY CAREGIVERS. (20th December 2022) - Browning, Wesley; Atkins, Ghislaine; Bowen, Pamela; Crowe, Michael; Dreer, Laura; Ruggiano, Nicole; Clay, Olivio
Abstract: Family caregivers provide care for loved ones who have difficulty performing activities of daily living. Previous research has examined the influence of direct and indirect stressors on caregiver's health outcomes but has often neglected the role of tertiary stressors (stressors that are not caused by caregiving but influence caregivers' appraisals of stress). This study examined the impact of tertiary stressors called adverse social experiences (ASEs), including negative interaction (criticism from others, excessive demands by others, being taken advantage of, and others prying into caregivers' personal affairs), experiences of discrimination, and low physician trust on caregiver health outcomes including depressive symptoms along with mental and physical health quality of life (QoL). This study also investigated the effects of social support on health outcomes in caregivers. Linear regression models were used to analyze these relationships within a group of 56 Black and White adult caregivers (18+) recruited online via social media and listservs from April to June 2021. Caregivers provided at least 5 hours of care weekly for recipients aged at least 45 years old. Negative interaction predicted more depressive symptoms, whereas emotional support and satisfaction with support were predictors of less depressive symptoms and better mental health QoL (p's < .05). Experiences of discrimination and physician trust did not predict health outcomes. These findings suggest researchers should further investigate the impact of ASEs, particularly negative interaction, on caregiver health. Healthcare providers of caregivers should consider how ASEs and social support may affect caregivers' health and ability to care for their relatives.